2021
DOI: 10.1016/j.envres.2020.110223
|View full text |Cite
|
Sign up to set email alerts
|

The spread of SARS-CoV-2 in Spain: Hygiene habits, sociodemographic profile, mobility patterns and comorbidities

Abstract: COVID-19 constitutes the largest pandemic in the last 100 years. In view of the rapid spread of the virus, it is necessary to study the sociodemographic characteristics, hygiene habits, activity and mobility, and comorbidities of SARS-CoV-2 infection to be able to implement prevention strategies. For this purpose, a survey including the variables of interest was designed to try to understand the exponential spread of the virus despite the implemented severe restrictive mobility measures during the period of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 30 publications
4
39
0
2
Order By: Relevance
“…In contrast, infections within lower socioeconomic groups may result from multiple sources. This observation aligns with the possibility that low socioeconomic status may relate to jobs requiring higher personal contact, and compulsory mobility 38 , which has been shown to increase the risk of infection by 76% 39 .…”
Section: Discussionsupporting
confidence: 81%
“…In contrast, infections within lower socioeconomic groups may result from multiple sources. This observation aligns with the possibility that low socioeconomic status may relate to jobs requiring higher personal contact, and compulsory mobility 38 , which has been shown to increase the risk of infection by 76% 39 .…”
Section: Discussionsupporting
confidence: 81%
“…Our results are similar to previous studies that have demonstrated the same trend in both child and adult patients [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. We can speculate that social-distancing measures, the use of face masks, hand washing, and the complete closure of social activities may have contributed not only to the reduction of SARS-CoV-2 diffusion [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ] but also to the reduction of the spread of other diseases, particularly of acute communicable diseases, as confirmed in a recent study [ 41 ]. Acute communicable diseases represent the most common clinical conditions in children; in fact, up to 11 respiratory tract infections per year in infancy, 8 episodes per year at pre-school age, and 4 episodes per year at school age could be considered as normal [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study has some limitations. First, no direct measures of social distancing or other strategies were taken in order to evaluate their contribution for reducing the spread of SARS-CoV-2 and other airborne infections, as other authors have done in previous studies [ 41 , 52 , 63 ]. Moreover, social distancing measures, the use of face masks, hand washing, and the complete closure of social activities were assumed to be followed.…”
Section: Discussionmentioning
confidence: 99%
“…In this document, guidance to prevent the introduction and spread of SARS-COV-2 in educational settings, to be taken at both school and classrooms levels, includes environmental measures as i) “maintaining clean environment: frequent cleaning of surfaces and shared objects”; and ii) “ensuring adequate and appropriate ventilation with priority for increased fresh outdoor air by opening windows and doors”. For instance, although sharing indoor space has been confirmed as a major risk factor in transmission of SARS-CoV-2 ( Allen and Marr, 2020 ; Qian et al, 2020 ; Rodríguez-Barranco et al, 2021 ), enhanced ventilation may be a key element in limiting the spread of the SARS-CoV-2 virus and other infectious agents in enclosed environments ( Li et al, 2007 ; Morawska et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%